PENINGKATAN KEMAMPUAN MENULIS NASKAH DRAMA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC DENGAN MEDIA KARTU SITUASI KHAYAL PADA SISWA KELAS VI-B SDN 1 BERINGIN RAYA - Indun Marwani (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
This study aims to: 1) improve the students' writing skills of SD Negeri 1 Beringin Raya, Kemiling District, Bandar Lampung City through the CIRC (Cooperative Integrated Reading and Composition) learning model and imaginary situation card media; 2) increasing behavior change in students of SD Negeri 1 Beringin Raya, Kemiling District, Bandar Lampung City in writing drama scripts through the CIRC (Cooperative Integrated Reading and Composition) learning model and imaginary situation card media. The method used is classroom action research. This classroom action research is expected to improve the quality of learning to write drama scripts. This research was conducted in three cycles, namely cycle I, cycle II and cycle III. The results showed that 1) learning to write drama scripts through the Cooperative Learning Model Type CIRC (Cooperative, Integrated, Reading, and Composition) and imaginary situation card media can help students improve their ability to write drama scripts; 2) The improvement of students' abilities in writing drama scripts is followed by changes in student behavior that lead to positive behavior.